Off-Pump Coronary Artery Bypass Graft - Ahmed, Mohamed S.; Neamah, Ahmed A.; Abed, Ali N. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Coronary artery bypass graft is routinely performed on an arrested heart using cardiopulmonary bypass with aortic cross clamping and Cardioplegia. Off-pump coronary artery bypass graft (OPCABG) is being increasingly used in selected cases as an attempt to decrease morbidity and mortality.Objective: The main objective of this study is to clarify those patients who are indicated for OPCABG despite it is surgically demanding technique and to evaluate the mortality and morbidity associated with such procedures.Patients and methods: It is a retrospective study of 28 patients with coronary artery disease, in need for coronary artery bypass graft admitted and surgically treated at the Iraqi Centre for Heart Diseases during 2 years period using OPCABG.Results : most of the patients were male (82%), and most of them (42%) were within age group of 61-70 years, the main indication of off-pump coronary artery bypass graft was left ventricular dysfunction and the least indication was cerebrovascular accident and renal impairment.Conclusion: Off-pump coronary artery bypass graft is useful in context of morbidity and mortality when indicated for patients with special criteria, those patients might get harm if we put them on bypass.